Motion Analysis of Simulated Patients During Bed-to-Wheelchair Transfer by Nursing Students and Skill Acquisition Based on the Analysis - Nakagawa, Hiromi; Tukamoto, Masahiro; Yamashiro, Kazuaki; Goto, Akihiko (Digital Human Modeling. Applications in Health, Safety, Ergonomics, and Risk Management, 2018)
The aging population in Japan is currently at 26.7% and is projected to reach 30.3% by 2025. This points to an increase in nursing care that involves transferring in and out of a wheelchair. Previous research has shown that the way a caregiver embraces the patient when transitioning her from bed to wheelchair contributes to lower back pain and has necessitated educational intervention to prevent occupational back pain. On the other hand, the patient is required to transfer into a wheelchair without falling and to maintain a seated position with the appropriate amount of body pressure. Both caregiver and receiver are asked to act in ways that are safe for both sides when transferring. In our own motion analysis of wheelchair transition, the non-experts bent forward more at the cervical and lumbar spine than the experts, creating greater body pressure distribution due to a smaller area of physical contact with the simulated patient. These results suggest that actions used for bed-to-wheelchair transferring influenced the seated position of the simulated patient. However, there are very few motion analysis studies that examine the patients’ movements during a wheelchair transfer. Therefore, this study is based on a motion analysis of the simulated patients while they are being transferred from bed to wheelchair. The study involves 4 nursing students who completed their practical training, and 2 expert nurses. The goal of this study is to turn into explicit knowledge and quantify the tacit techniques of position changing performed in nursing care. Results of this study show that the simulated patients transferred by the non-experts were led through the seating phase faster than those transferred by the experts, and the increase in speed was related to the nurses’ proximity to their simulated patients. Furthermore, we learned that motion analysis could be applied to skill acquisition.